2021
DOI: 10.3389/fphar.2021.651050
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic and Stochastic Cellular Mechanisms Contributing to Carbon Monoxide Induced Ventricular Arrhythmias

Abstract: Chronic exposure to low levels of Carbon Monoxide is associated with an increased risk of cardiac arrhythmia. Microelectrode recordings from rat and guinea pig single isolated ventricular myocytes exposed to CO releasing molecule CORM-2 and excited at 0.2/s show repolarisation changes that develop over hundreds of seconds: action potential prolongation by delayed repolarisation, EADs, multiple EADs and oscillations around the plateau, leading to irreversible repolarisation failure. The measured direct effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Although guinea pig left ventricular myocytes have a similar AP duration at 90% of the repolarization (APD90) ( Beserra et al, 2020 ; Al-Owais et al, 2021 ) to the rabbit APD, they lack the transient outward potassium current ( I to ) ( Hoppe et al, 1999 ), which is critical for early phase 1 repolarization during the cardiac AP ( Varro et al, 1993 ; Dixon et al, 1996 ). However, when Kv4.3 was artificially introduced and I to could be recorded from the guinea pig myocytes, the guinea pig APD decreased dramatically ( Hoppe et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although guinea pig left ventricular myocytes have a similar AP duration at 90% of the repolarization (APD90) ( Beserra et al, 2020 ; Al-Owais et al, 2021 ) to the rabbit APD, they lack the transient outward potassium current ( I to ) ( Hoppe et al, 1999 ), which is critical for early phase 1 repolarization during the cardiac AP ( Varro et al, 1993 ; Dixon et al, 1996 ). However, when Kv4.3 was artificially introduced and I to could be recorded from the guinea pig myocytes, the guinea pig APD decreased dramatically ( Hoppe et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although guinea pig left ventricular myocytes have an action potential (AP) duration (APD90) ( Beserra et al, 2020 ; Al-Owais et al, 2021 ) similar to rabbit APD90, they lack transient outward potassium current ( I to ) ( Hoppe et al, 1999 ), which is critical for early phase 1 repolarization during the cardiac AP ( Varro et al, 1993 ; Dixon et al, 1996 ). In larger mammals, I to establishes the membrane potential for Ca 2+ entry and influences APD, and changes in I to may underlie ventricular tachycardia ( Choi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The QTd reflects the transmural heterogeneities of repolarization time within ventricles, and the heterogeneities are secondary to regional differences in APD and activation time (122). Recent simulation studies suggested that the increased transmural dispersion of repolarization (TDR) by CO was attributed to the more prolonged APD in midmyocardial cells comparing to epicardial or endocardial cells (123,124), and the different APD changes may arise from the heterogeneous current densities in different cell types (125). The increased TDR then contributes to higher risks of developing unidirectional conduction block (measured as the vulnerable window), and finally leads to TdP, reentry arrhythmias, and VF (126).…”
Section: Potential Proarrhythmic Mechanismsmentioning
confidence: 99%
“…In the case of CO, the clinically observed Pwd may originate from several ionic remodeling effects. First, CO could decrease the conduction velocity of excitation wave (123,124); therefore the intra-and interatrial conduction times of sinus node impulses can be prolonged. Such assumption is based on the fact that CO could inhibit I Na (111).…”
Section: Potential Proarrhythmic Mechanismsmentioning
confidence: 99%
“…Such arrhythmogenic influences may get even worse in susceptible populations like heart failure (HF) patients. This is because the repolarization reserve has been reduced in failing hearts, and the further depression of I Kr by CO can easily lead to early-afterdepolarization (EAD) activities in cardiomyocytes and ectopic beats at the organ level, which act as triggers for reentry arrhythmias ( Al-Owais et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%